2020
DOI: 10.2139/ssrn.3617421
|View full text |Cite
|
Sign up to set email alerts
|

The Finance of Unemployment Compensation and its Consequence for the Labor Market

Abstract: Any opinions expressed in this paper are those of the author(s) and not those of IZA. Research published in this series may include views on policy, but IZA takes no institutional policy positions. The IZA research network is committed to the IZA Guiding Principles of Research Integrity. The IZA Institute of Labor Economics is an independent economic research institute that conducts research in labor economics and offers evidence-based policy advice on labor market issues. Supported by the Deutsche Post Founda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 61 publications
(77 reference statements)
0
2
0
Order By: Relevance
“…In theKaplan and Violante (2014) model, the availability of a high-return illiquid asset with a transaction cost leads agents to hold relatively few liquid assets. It seems likely that an agent in their model with few liquid assets who did not access her illiquid asset would behave similarly to the agent with zero assets at onset in our model, while an agent who did access her illiquid asset would not dramatically cut spending at exhaustion 32. Stephens and Toohey (2018) reexamine this result using a wide range of dietary intake surveys.…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…In theKaplan and Violante (2014) model, the availability of a high-return illiquid asset with a transaction cost leads agents to hold relatively few liquid assets. It seems likely that an agent in their model with few liquid assets who did not access her illiquid asset would behave similarly to the agent with zero assets at onset in our model, while an agent who did access her illiquid asset would not dramatically cut spending at exhaustion 32. Stephens and Toohey (2018) reexamine this result using a wide range of dietary intake surveys.…”
mentioning
confidence: 72%
“…A final strand of the literature has suggested that the drop in spending at retirement may be attributable to increased home production (Aguiar and Hurst 2005). 32 Because benefit exhaustion is a change in income without a change in the agent's time budget, the observed drop in spending cannot be explained by a change in home production.…”
Section: Why the Drop At Exhaustion Is Hard To Fit With Any Rational Forward-lookingmentioning
confidence: 99%